Consulting services for vocational education and training in the Gulf States : an explorative study on demand, arrangement and perception of consultancy - Klein, Paula [Verfasser]; Pilz, Matthias [Verfasser] (My University, 2026)
„The vocational education and training (VET) consulting market is growing rapidly in the Arab Gulf States but still remains under-researched. This exploratory study examines its structure and characteristics through 12 qualitative interviews with private consultants and company representatives, focussing on the drivers of demand, the arrangement of these services and how they are perceived. Findings reveal that demand stems from government-led economic diversification, workforce development initiatives and align education with international standards. Large consultancy firms dominate strategic and VET policy-level work, while smaller firms and individual consultants handle operational support. Interviewees report divergent views on transparency and concerns about localisation of international models. By providing a first systematic account of commercial consulting for VET in this region, the study illuminates how private actors shape vocational educational policy in resource-rich nations pursuing rapid modernisation.” (authors’ abstract; BIBB-Doku)
Keywords: I 2.3.4 Asien; 370; Berufsbildung; Bildungsberatung; Interview; Arabische Länder